Makna dan Martabat Kerja: Perspektif Filsafat Manusia dalam Era Kapitalisme Global: The Meaning and Dignity of Work: A Philosophical Perspective on Humanity in the Era of Global Capitalism - Dewi, Amalia Rusti Mutiara (Undiksha, 2025)
This study investigates the significance and dignity of work through the lens of humanism, particularly in the context of global capitalism. In this perspective, the meaning of labor is not just seen as an economic activity, but also as an intrinsic component of the human experience and the quest for meaning in life. This paper explores the impact of global capitalism on the meaning and dignity of work, and offers philosophical reflections on how humans can find significance in the changing world of work. Historical and economic approaches provide a framework for understanding how capitalism emerged and developed over time. Economists such as Adam Smith have outlined the basic principles of capitalism, including free markets and individual freedom. However, other thinkers such as Karl Marx have criticized capitalism as a system based on exploitation and domination. There is also analysis of the psychological and social nature of capitalism. Some theories suggest that capitalism is driven by the human drive to accumulate wealth and power. This leads us to the conclusion that capitalism is more than just an economic system; it is also a social and cultural system that shapes how we perceive ourselves and our interactions with others. Reflections on how humans might find purpose in a changing world of work.